ZAITUN POHON YANG DIBERKAHI YANG MEMILIKI BERAGAM KEISTIMEWAAN: ZAITUN POHON YANG DIBERKAHI YANG MEMILIKI BERAGAM KEISTIMEWAAN - Fauziah, Syifa (JURNAL KESEHATAN STIKes MUHAMMADIYAH CIAMIS, 2022)
The COVID-19 pandemic that is currently happening in the world is causing anxiety for the world community. Various efforts have been made to prevent the spread of the COVID-19 virus. As the spread of the covid-19 virus spreads so quickly, it is recommended that COVID- 19 sufferers to speed up the discovery of traditional medicines as a treatment by using one of the herbal medicines, namely olive. Olives are plants that are blessed by Allah SWT. which has many advantages. There are also many in the Qur'an that explain the benefits of olives for health. So to prevent the Covid-19 virus. The method used is Systematic Literature Review (SLR). The purpose of this study was to determine that olives are antioxidants. The results of the study show that olives contain phenols which are efficacious as antioxidants or free radical scavengers and also to improve the immune system.